Predicting Post-Operative Side Effects in VIM MRgFUS Based on THalamus Optimized Multi Atlas Segmentation (THOMAS) on White-Matter-Nulled MRI: A Retrospective Study - Oshima, Sonoko; Kim, Asher; Sun, Xiaonan R.; Rifi, Ziad; Cross, Katy A.; Fu, Katherine A.; Salamon, Noriko; Ellingson, Benjamin M.; Bari, Ausaf A.; Yao, Jingwen (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Precise and individualized targeting of the ventral intermediate thalamic nucleus for the MR-guided focused ultrasound is crucial for enhancing treatment efficacy and avoiding undesirable side effects. In this study, we tested the hypothesis that the spatial relationships between Thalamus Optimized Multi Atlas Segmentation derived segmentations and the post-focused ultrasound lesion can predict post-operative side effects in patients treated with MR-guided focused ultrasound.MATERIALS AND METHODS: We retrospectively analyzed 30 patients (essential tremor, n = 26; tremor-dominant Parkinson’s disease, n = 4) who underwent unilateral ventral intermediate thalamic nucleus focused ultrasound treatment. We created ROIs of coordinate-based indirect treatment target, focused ultrasound-induced lesion, and thalamus and ventral intermediate thalamic nucleus segmentations. We extracted imaging features including 1) focused ultrasound-induced lesion volumes, 2) overlap between lesions and thalamus and ventral intermediate thalamic nucleus segmentations, 3) distance between lesions and ventral intermediate thalamic nucleus segmentation and 4) distance between lesions and the indirect standard target. These imaging features were compared between patients with and without post-operative gait/balance side effects using Wilcoxon rank-sum test. Multivariate prediction models of side effects based on the imaging features were evaluated using the receiver operating characteristic analyses.RESULTS: Patients with self-reported gait/balance side effects had a significantly larger extent of focused ultrasound-induced edema, a smaller fraction of the lesion within the ventral intermediate thalamic nucleus segmentation, a larger fraction of the off-target lesion outside the thalamus segmentation, a more inferior centroid of the lesion from the ventral intermediate thalamic nucleus segmentation, and a larger distance between the centroid of the lesion and ventral intermediate thalamic nucleus segmentation (p < 0.05). Similar results were found for exam-based side effects. Multivariate regression models based on the imaging features achieved areas under the curve of 0.99 (95% CI: 0.88 to 1.00) and 0.96 (95% CI: 0.73 to 1.00) for predicting self-reported and exam-based side effects, respectively.CONCLUSIONS: Thalamus Optimized Multi Atlas Segmentation-based patient-specific segmentation of the ventral intermediate thalamic nucleus can predict post-operative side effects, which has implications for aiding the direct targeting of MR-guided focused ultrasound and reducing side effects.AC-PCanterior commissure-posterior commissureAUCareas under the curveETessential tremorFGATIRFast Gray Matter Acquisition T1 Inversion RecoveryFTMFahn-Tolosa-Marín Clinical Rating Scale for TremorMRgFUSMR-guided focused ultrasoundPDParkinson’s diseaseTHOMASTHalamus Optimized Multi Atlas SegmentationTHthalamusVIMventral intermediate nucleus